Electrical potentials developed during thawing of frozen ground - Parameswaran, V. R.; Johnston, G. H.; MacKay, J. R. (1985)
Electrical potentials developed during thawing of the active layer in frozen ground have been measured at a test site in Inuvik, Northwest territories. Probes containing copper electrodes spaced at regular intervals were installed vertically in a clay hummock, in an ice-rich soil at the junction of three hummocks, and in a sandy gravel and reconstituted clay in wax-coated cardboard tubes placed in an adjacent hummock. The maximum voltage measured across the thaw boundary was of the order of 500mV in the fine- grained soil and about 200mV in the coarse-grained soil. The difference may be due to the larger amounts of moisture in the fine-grained soil. Les auteurs ont mesuré les potentiels électriques produits lors du dégel du mollisol dans un site expérimental situé à Inuvik, dans les Territoires du Nord-Ouest. On a installé verticalement des sondes contenant des électrodes de cuivre disposées à intervalles réguliers dans un tertre argileux, dans un sol riche en glace à la jonction de trois tertres, ainsi que dans des tubes de carton enduits de cire, l'un rempli de gravier sableux et l'autre d'argile reconstitué, et plantés dans un tertre adjacent. La tension maximale mesurée de part et d'autre de la limite de la zone de dégel était de l'ordre de 500mV dans le sol fin et d'environ 200mV dans le sol grossier. La différence découle peut-être du plus fort degré d'humidité du sol fin. Peer reviewed: Yes NRC publication: Yes